EX VIVO TERAHERTZ IMAGING REFLECTION OF MALIGNANT AND BENIGN HUMAN BREAST TUMORS - Amel Al-Ibadi (Malaysian Journal of Science, 2022)
This study evaluated the effectiveness of spectroscopy and imaging tools, using a previously-unexplored (0.2- 1.4) terahertz range, for investigating tumors in human tissue and distinguishing between malignant and benign cancer cells. One advantage of this technique is that terahertz radiation in this frequency range passes through human tissue without causing ionization or any negative effects To assess the effectiveness of this band of frequencies, THz data were collected from 10 different fresh breast tissue samples, extracted directly after excision. The optical properties were investigated at a range of low frequencies and THz imaging revealed good contrast between the different types of fresh tissue. Observations indicated that the optical and electrical properties in the low-frequency (0.3-0.5) range provided accurate information about breast cancer tissue. These results demonstrated the effectiveness of the technique up to 0.5 THz for ex vivo studies in medical applications.